Long-term tolerability and efficacy of golimumab in active non-radiographic axial spondyloarthritis: results from open-label extension. (20th April 2021) - van der Heijde, Désirée; Dougados, Maxime; Maksymowych, Walter P; Bergman, Gina; Curtis, Sean P; Tzontcheva, Anjela; Huyck, Susan; Philip, George; Sieper, Joachim
Abstract: Objectives: We report the open-label extension (OLE) of the GO-AHEAD study evaluating the long-term efficacy and safety of golimumab (GLM) in patients with non-radiographic axial spondyloarthritis (nr-axSpA). Methods: Patients [both GLM- and placebo (PBO)-treated in the double-blind phase] received GLM 50 mg every 4 weeks during the OLE (36-week treatment; additional 8-week safety follow-up; GLM/GLM and PBO/GLM groups). All patients who entered and received ≥1 dose of study treatment in the OLE were included in the efficacy and safety analyses. The primary efficacy evaluations were the proportions of patients achieving 20% and 40% improvement in the ASAS criteria (ASAS20 and ASAS40, respectively). Responders' analyses were calculated using a non-responder imputation approach. Results: Of 198 patients randomised, 189/198 (95.5%) entered the OLE; 174/198 patients (87.9%) completed all visits. Although the proportion of responders increased from week 16 to week 52 in the OLE in both GLM/GLM and PBO/GLM groups, the GLM/GLM group had a higher proportion of responders than the PBO/GLM group throughout the OLE from week 16 to week 52 (ASAS20: 71.1% to 83.9% vs 40.0% to 75.0%, respectively; ASAS40: 56.7% to 76.3% vs 23.0% to 59.4%, respectively; ASAS partial remission: 33.0% to 53.8% and 18.0% to 45.8%). In the OLE, the overall incidence of AEs was lower in the GLM/GLM vs PBO/GLM groups (41.9% and 54.2%). Conclusions: Sustained improvement in clinical efficacy was observed at 52 weeks in patients with nr-axSpA following GLM treatment. GLM was well tolerated and provided substantial long-term benefits to patients with nr-axSpA. Trial registration: NCT01453725; United States National Library of Medicine clinical trials database; www.clinicaltrials.gov .